Corporate Culture, Transformational Charismatic Leadership and Cooperative Performance: Lessons from Indonesia - Hidayat, Yusuf; Nur, Rahmat; Nurdiyana, Tutung; Suharnanik, Suharnanik (Journal of Ecohumanism, 2024)
Cooperatives often suffer from negative perceptions due to low performance. However, the Sawit Makmur Cooperative in Tanah Laut Regency has excelled and improved member welfare through a strong corporate culture and effective leadership. This study explores the corporate culture of Sawit Makmur and analyzes the role of transformative charismatic leadership in its success. Using qualitative methods, research was conducted at the cooperative in Pelaihari City, South Kalimantan Province. Subjects were purposively selected, and data was collected via observation, in-depth interviews, and field notes. The findings indicate that (1) Cooperatives perform well when they have a corporate culture characterized by integrity, professionalism, and a humane approach. (2) This culture is supported by the commitment and collaborative spirit of both management and members, driven by transformative charismatic leadership. This leadership style nurtures and sustains the corporate culture, significantly enhancing cooperative performance. The research highlights that effective cooperatives must develop a corporate culture of integrity, professionalism, and humanity. Future studies should compare cooperatives with and without corporate cultures in macro-finance contexts to further understand the impact of cultural attributes on performance.